Inadequate Control of Diabetes and Metabolic Indices among Diabetic Patients: A Population Based Study from the Kerman Coronary Artery Disease Risk Study (KERCADRS) - Gholamreza Yousefzadeh; Mostafa Shokoohi; Hamid Najafipour (Kerman University of Medical Sciences, 2015)
Background The goal of diabetes control should be feasible in order to minimize the risk of its adverse events and to reduce its burden and cost on patients. The current study aimed to assess the status of glycemic control in male and female patients with Type 2 Diabetes Mellitus (T2DM) in Kerman, Iran. Methods In the present study, 500 T2DM (300 women and 200 men) from the Kerman Coronary Artery Disease Risk Study (KERCADRS), a population-based study from 2009 to 2011, were selected. Patients were >18 years old, had Fasting Blood Sugar (FBS) higher than 126 mg/dl, and had been through treatment for their diagnosed disease. All participants underwent Glycosylated Hemoglobin (HbA1c) analysis. HbA1c less than 7% was considered as good glucose control. Other metabolic indices based on American Diabetes Association (ADA) target recommendations were considered. Results The mean level of HbA1c in total subjects was 8.56 ± 4.72% that only 31.66% of men and 26.00% of women had controlled level of HbA1c. Total cholesterol less than 200 mg/dl was reported in 64.50% of men and 44.00% of women, High Density Lipoprotein (HDL) more than 40 mg/dl was revealed in 20.50% of men and 34.67% of women, and Low Density Lipoprotein (LDL) less than 100 mg/dl was reported in 41.50% of men and 25.33% of women. In multivariate logistic regression model, longer duration of disease and higher Waist Circumference (WC) were positively associated with uncontrolled diabetes status. Conclusion The findings of the present study revealed that diabetes control in T2DM was inadequate. Changing the policy of treatment in individual patient and establishing better diabetes clinic to decrease the frequency of uncontrolled T2DM are crucial. Paying attention to other affecting metabolic components such as WC in the process of T2DM management is important.